Economic Analysis of Transactions in the Energy Storage Power Market: A Life-Cycle Cost Approach - Dai, Shuangfeng; Ye, Ze; Wei, Wen; Wang, Yali; Jiang, Fei (Frontiers in Energy Research, 2022)
Aiming at the impact of energy storage investment on production cost, market transaction and charge and discharge efficiency of energy storage, a research model of energy storage market transaction economic boundary taking into account the whole life cycle cost was proposed. Firstly, a peak-valley filling time division method based on equal capacity is proposed, which effectively improves the peak-valley time division and the accuracy of ES should scene switch. On this basis, a control strategy of "off-time reuse" is proposed to give full play to the function of "one standby multi-purpose" of energy storage, which improves the energy storage utilization rate and economic benefits. Secondly, an economic boundary model based on the life-cycle cost of energy storage and the evolution function of energy storage cost is constructed and solved by improved genetic algorithm. Finally, the simulation results show that compared with mono-peak control, the UTILIZATION rate of ES is increased by 16.25% and the investment recovery life is shortened by 1.17 years with "off-time reuse" strategy. Compared with the fixed division method, the investment recovery life of "peak clipping and valley filling" period division method is shortened by 1.75 years. In 2022, compared with the critical value of 0.76 yuan /kWh for fixed charge-discharge efficiency and cost, the critical value of the life-cycle cost model is 0.8 yuan /kWh, with an error of up to 5.26%.